Lightning flashover rates of overhead distribution lines applying EMTP and IEEE std.1410 - Thanaphong Thanasaksiri (2018)
This paper calculates the lightning flashover rates of 22 kV overhead distribution line. In order to calculate the backflashover rate (BFOR), the performance of line which related to the insulator backflashover has been modeled and analyzed using Electromagnetic Transient Program (EMTP). The flashover models, volt time curve (VT), disruptive effect model (DE) and leader progression model (LPM) have been compared. The shielding failure flashover rate (SFFOR) and induced voltage flashover rate (IVFOR) have been calculated follow equations given in IEEE std 1410-2010. Finally the total numbers of flashovers of line have been determined. The lightning flashovers rates of BFOR, SFFOR and IVFOR have also been compared with the data taken from the line outages recorder. From the system being studied shown that, the total numbers of flashovers from simulation and calculation is closed to the data from the line outage recorder.